In vitro anti-Trichomonas vaginalis activity of Haplophyllum myrtifolium - Aysegul A Gokmen; Hüseyin Can; Hüsniye Kayalar; Bayram Pektaş; Selçuk Kaya (Journal of Infection in Developing Countries)
Introduction: In the classic treatment of Trichomonas vaginalis infection, although metronidazole has been used since the 1960s, there has been an increase in MTZ-resistant T. vaginalis strains and failure in the treatment of trichomoniasis causes serious concerns. Therefore, the present study aimed to investigate the in vitro antitrichomonal activities of extracts (ethanol and total alkaloid) and pure compounds (chrysosplenetin, dictamnine, gamma-Fagarine, skimmianine) of H. myrtifolium against T. vaginalis.